Improving Income from Coconut Cultivation through Farm Level Value Addition – An Analysis - Anithakumari, P.; Rajeev, M. S.; George, Jissy (International Coconut Community, 2012)
Coconut cultivation in India is mostly in small and marginal land holdings. Farm level coconut processing for value addition is one of the options for risk reduction and improving the income from such holdings. This study was conducted during 2009-10 with the objectives of analyzing the profile of farm level processors as well as the constraints faced by those who have adopted minimal processing at the farm-household and community levels. It was found that 63.3% of the respondents were of middle age group, literate, low income group and 80% of them were women. The experience in coconut value addition was for 8 years or less. Further, the entrepreneurship behavior of the respondents was found to be positively and significantly correlated with the credit availed, annual income and investment made. The analysis on the utility of the training programmes indicated need for reorientation of training curricula in terms of project preparation techniques, communication/marketing skills etc. The value addition obtained per nut was found to vary from Rs.0.5 to Rs.15 depending on the products. The constraints and suggestions for improving farm level value addition were also furnished as perceived by the respondent farmers. The study showed that there is tremendous potential for farm level value addition for utilizing the marketable surplus of coconut locally. The importance of providing further technical support to those involved in value addition was also revealed by the study.